Implementation Of Gender Mainstreaming Policies In Regional Development In East Kalimantan Province - Nadia Istamala; Cathas Teguh Prakoso; Muh. Jamal Amin (JURNAL ECONOMINA, 2026)
Gender Mainstreaming is a development strategy aimed at achieving gender equality through the integration of gender perspectives into every stage of regional development. Although the Government of East Kalimantan Province has enacted Regional Regulation Number 5 of 2024 concerning Gender Mainstreaming in Regional Development, its implementation still encounters several challenges, including limited inter-agency coordination, inadequate human resource capacity, and uneven understanding of Gender Responsive Planning and Budgeting. This study aims to analyze the implementation of Gender Mainstreaming policy in regional development in East Kalimantan Province and identify the supporting and inhibiting factors affecting its implementation. A qualitative descriptive approach was employed using interviews, observation, and documentation techniques. Data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña. The implementation analysis adopted George C. Edward III's policy implementation model consisting of communication, resources, disposition, and bureaucratic structure. The findings reveal that the implementation of Gender Mainstreaming policy has generally been effective. Communication has been carried out through regular dissemination, technical assistance, and monitoring. Resources are supported by adequate regulations, institutional arrangements, the Klik SiGen application, and increasing Gender Responsive Budget allocations, although human resource capacity remains a challenge. The disposition dimension reflects the commitment of local government institutions and strategic partnerships in promoting gender equality. The bureaucratic structure has been strengthened through Gender Mainstreaming Working Groups, Gender Focal Points, Driver Teams, and cross-sector coordination mechanisms. Supporting factors include regulatory commitment, institutional capacity, and collaborative governance, whereas the main constraints involve limited human resources, inadequate gender-disaggregated data, and the misconception that Gender Mainstreaming is solely the responsibility of the Women's Empowerment and Child Protection Office.